Evaluation of Health-Related Quality of Life In Children With Vernal Keratoconjunctivitis Using Quality Of Life In Children With Vernal Keratoconjunctivitis Questionnaire - Khusus, Khairil Ridzwan Kamalul (2021)
INTRODUCTION Vernal keratoconjunctivitis (VKC) is a recurrence, and chronic bilateral ocular allergic conjunctivitis mainly affected male prepuberty children. The signs and symptoms of VKC given a negative impact on well-being, lifestyle and limitation on psychosocial activities. There has been a lack of data on health-related quality of life (HRQoL) in children with VKC from Southeast Asia.